# |
ODE |
Mathematica |
Maple |
\[
{}x^{\prime } = x \left (1-\frac {x}{4}\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x^{2}+t^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = t \cos \left (t^{2}\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {t +1}{\sqrt {t}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = t \,{\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {1}{t \ln \left (t \right )}
\] |
✓ |
✓ |
|
\[
{}\sqrt {t}\, x^{\prime } = \cos \left (\sqrt {t}\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {{\mathrm e}^{-t}}{\sqrt {t}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = {\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}u^{\prime } = \frac {1}{5-2 u}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = a x+b
\] |
✓ |
✓ |
|
\[
{}Q^{\prime } = \frac {Q}{4+Q^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = {\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = r \left (a -y\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {2 x}{t +1}
\] |
✓ |
✓ |
|
\[
{}\theta ^{\prime } = t \sqrt {t^{2}+1}\, \sec \left (\theta \right )
\] |
✓ |
✓ |
|
\[
{}\left (2 u+1\right ) u^{\prime }-t -1 = 0
\] |
✓ |
✓ |
|
\[
{}R^{\prime } = \left (t +1\right ) \left (1+R^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y+\frac {1}{y} = 0
\] |
✓ |
✓ |
|
\[
{}\left (t +1\right ) x^{\prime }+x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{2 y+1}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \left (4 t -x\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 2 t x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = t^{2} {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x \left (4+x\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = {\mathrm e}^{t +x}
\] |
✓ |
✓ |
|
\[
{}T^{\prime } = 2 a t \left (T^{2}-a^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2} \tan \left (y\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {\left (4+2 t \right ) x}{\ln \left (x\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 t y^{2}}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {t^{2}}{1-x^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 6 t \left (x-1\right )^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {4 t^{2}+3 x^{2}}{2 t x}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } {\mathrm e}^{2 t}+2 x \,{\mathrm e}^{2 t} = {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}+2 t y}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -y^{2} {\mathrm e}^{-t^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 2 t^{3} x-6
\] |
✓ |
✓ |
|
\[
{}\cos \left (t \right ) x^{\prime }-2 x \sin \left (x\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = t -x^{2}
\] |
✓ |
✓ |
|
\[
{}7 t^{2} x^{\prime } = 3 x-2 t
\] |
✓ |
✓ |
|
\[
{}x x^{\prime } = 1-t x
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -\frac {2 x}{t}+t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+2 t x = {\mathrm e}^{-t^{2}}
\] |
✓ |
✓ |
|
\[
{}t x^{\prime } = -x+t^{2}
\] |
✓ |
✓ |
|
\[
{}\theta ^{\prime } = -a \theta +{\mathrm e}^{b t}
\] |
✓ |
✓ |
|
\[
{}\left (t^{2}+1\right ) x^{\prime } = -3 t x+6 t
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+\frac {5 x}{t} = t +1
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \left (a +\frac {b}{t}\right ) x
\] |
✓ |
✓ |
|
\[
{}R^{\prime }+\frac {R}{t} = \frac {2}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}N^{\prime } = N-9 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}\cos \left (\theta \right ) v^{\prime }+v = 3
\] |
✓ |
✓ |
|
\[
{}R^{\prime } = \frac {R}{t}+t \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+a y = \sqrt {t +1}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 2 t x
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+\frac {{\mathrm e}^{-t} x}{t} = t
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \left (t +x\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = a x+b
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+p \left (t \right ) x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {2 x}{3 t}+\frac {2 t}{x}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x \left (1+x \,{\mathrm e}^{t}\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -\frac {x}{t}+\frac {1}{t x^{2}}
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime }+2 t y-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = a x+b x^{3}
\] |
✓ |
✓ |
|
\[
{}w^{\prime } = t w+t^{3} w^{3}
\] |
✓ |
✓ |
|
\[
{}x^{3}+3 t x^{2} x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{3}+\frac {x}{t}+\left (x^{2}+\ln \left (t \right )\right ) x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -\frac {\sin \left (x\right )-x \sin \left (t \right )}{t \cos \left (x\right )+\cos \left (t \right )}
\] |
✓ |
✓ |
|
\[
{}x+3 t x^{2} x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}-t^{2} x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t \cot \left (x\right ) x^{\prime } = -2
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+5 x = \operatorname {Heaviside}\left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+x = \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 2 x+\operatorname {Heaviside}\left (t -1\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x-2 \operatorname {Heaviside}\left (t -1\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -x+\operatorname {Heaviside}\left (t -1\right )-\operatorname {Heaviside}\left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+3 x = \delta \left (t -1\right )+\operatorname {Heaviside}\left (t -4\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 1+x
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime }+x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x^{3} y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = 3 x^{2} {\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 x y = 8 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 6 \,{\mathrm e}^{x}+4 x \,{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2 x \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2 x \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} \sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}}{x -2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}3 x +2 y+\left (y+2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+3+\left (2 x y-4\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y+1+\left (x^{2}+4 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y+2-\left (x^{3}+y\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}6 x y+2 y^{2}-5+\left (3 x^{2}+4 x y-6\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \sec \left (x \right )^{2}+\sec \left (x \right ) \tan \left (x \right )+\left (\tan \left (x \right )+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x}{y^{2}}+x +\left (\frac {x^{2}}{y^{3}}+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {\left (2 s-1\right ) s^{\prime }}{t}+\frac {s-s^{2}}{t^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2 y^{{3}/{2}}+1}{\sqrt {x}}+\left (3 \sqrt {x}\, \sqrt {y}-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y-3+\left (x^{2}+4 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|